Strengthening Islamic Religious Literacy and Children’s Communication Skills through Inter-Qur’anic Education Center Competition Activities - Hayeeyusoh, Ausamah; Hamid, Azizah; Febyola, Chelyn; Hardi, Luthfiatul Hasanah; Rahmi, Maulia Adinda; Al-Halim, Muhammad; Firras, Muhammad; Junaldi, Muhammad; Fitri, Nadila Rahma; Hasna, Refha; Rianti, Rinda; Azzahra, Siti Fatimah; Nurazizah, Zahra Darfi; Romli, R. Cecep (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Inter-Qur’anic Education Center (Taman Pendidikan Al-Qur’an/TPA) competition activities represent a form of student community service in the fields of education and religion. Low levels of Islamic religious literacy and limited communication skills among children in TPA remain prevalent, particularly with regard to basic understanding of Islamic teachings, social relationships, and interpersonal interaction. These conditions are closely related to the continued use of conventional and less varied learning methods. This community service program was implemented through inter-TPA competition activities aimed at strengthening children’s Islamic religious literacy, fostering social interaction, and enhancing communication between students (santri) and instructors (ustadz). The program employed a participatory and collaborative approach, implemented through several stages, including planning, coordination with TPA administrators, execution of competition activities, and evaluation of outcomes. Data were collected through observation, discussion, and documentation, while data analysis was conducted using a qualitative descriptive method. The results indicate that the program successfully increased children’s motivation to learn Islamic teachings, strengthened solidarity among TPAs, and fostered Islamic values among participants. Therefore, inter-TPA competition activities can be considered an effective method for strengthening Islamic religious literacy and improving children’s communication skills.